The icmF3 locus is involved in multiple adaptation- and virulence-related characteristics in Pseudomonas aeruginosa PAO1 - Lin, Jinshui; Cheng, Juanli; Chen, Keqi; Guo, Chenghao; Zhang, Weipeng; Yang, Xu; Ding, Wei; Ma, Li; Wang, Yao; Shen, Xihui (Frontiers in Cellular and Infection Microbiology, 2015)
The type VI secretion system (T6SS) is widely distributed in Gram-negative bacteria. Three separate T6SSs called H1-, H2-, and H3-T6SS have been discovered in Pseudomonas aeruginosa PAO1. Recent studies suggest that, in contrast to the H1-T6SS that targets prokaryotic cells, H2- and H3-T6SS are involved in interactions with both prokaryotic and eukaryotic cells. However, the detailed functions of T6SS components are still uncharacterized. The intracellular multiplication factor (IcmF) protein is conserved in type VI secretion systems (T6SS) of all different bacterial pathogens. Bioinformatic analysis revealed that IcmF3 in P. aeruginosa PAO1 is different from other IcmF homologs and may represent a new branch of these proteins with distinct functions. Herein, we have investigated the function of IcmF3 in this strain. We have shown that deletion of the icmF3 gene in P. aeruginosa PAO1 is associated with pleiotropic phenotypes. The icmF3 mutant has variant colony morphology and an hypergrowth phenotype in iron-limiting medium. Surprisingly, this mutant is also defective for the production of pyoverdine, as well as defects in swimming motility and virulence in a C. elegans worm model. The icmF3 mutant exhibits higher conjugation frequency than the wild type and increased biofilm formation on abiotic surfaces. Additionally, expression of two phenazine biosynthetic loci is increased in the icmF3 mutant, leading to the overproduction of pyocyanin. Finally, the mutant exhibits decreased susceptibility to aminoglycosides such as tobramycin and gentamicin. And the detected phenotypes can be restored completely or partially by trans complementation of wild type icmF3 gene. The pleiotropic effects observed upon icmF3 deletion demonstrate that icmF3 plays critical roles in both pathogenesis and environmental adaptation in P. aeruginosa PAO1.